Жанрова специфіка треворової новели: українські перегуки - Кабкова, Ольга (Київський національний університет імені Тараса Шевченка, 2018)
Наведено роздуми про неоднозначність визначення новели, її жанрову гнучкість. Ураховано погляди В. Тревора на малу прозу; звернено увагу на збереження традиції та експериментування у його новелі. Аналіз окремих оповідок письменника унаочнює характеристичні ознаки його малої прози. Із багатої палітри сучасних українських новелістів обрано В. Трубая, чия мала проза співвідносна з доробком В. Тревора.

Analyzing the genre peculiarities of W.Trevor's stories we are to determine "short story", as this genre is not similar to "novela" or "opovidannia" in Ukrainian tradition. Moreover, the writers create their own genre significations. Besides, it should be taken into consideration the critics' opinion that the short story can be anything the author decides it is. The last statement echoes Ts.Todorov's and M.Blanchot's ideas about the modern genre flexibility. But even Ts.Todorov considers that the genre norm becomes vivid due to its violation. We do not regard Trevor's short story as such which is to have all the distinctive marks of this genre. Trevor's aesthetic preferences did not permit genre relativity. Canon was needful for him (G.Fowles' naming him the Irish Maupassant illustrated this feature). But there was a certain freedom in this applying the standard. Irish and English aspects were connected in the personality of the writer. His Irish-like love to storytelling, his loyalty to the reader's desire to find out what was going to happen next was in harmony with his extraordinary narrative skill, but also the remoteness of his storytelling favour should be mentioned. He told stories, offering fictional "realities" in a clear, matter-of-fact style without "philosophizing speculation or arguments for a particular political point of view". Thus he handed down Irish folk tradition, followed the tradition of the XX century Irish realistic short story and the English realistic prose of the XIX century. He defined himself as the "the least experimental of writers", but also said that he had experimented all the time though the experiments were hidden. He characterized the short story as "the art of the glimpse…an impressionist painting… an explosion of truth. Its strength lies in what it leaves out just as much as what it puts in, if not more…" So the most important feature of this genre is the poetry of much in little. Not less valid are imagination and impression in the Trevor's short stories. The plot of "Teresa's Wedding" progresses in a provincial location – one of Irish towns. The pregnant bride has to marry someone; it matters little who it may be. Trivial affair is without passion, imagination, illusions. The final episodes of the wedding are signed with confetti, covering all around. These confetti color dots are similar to Joyce's dust in "Eveline". Here are a commonplace atmosphere and impressionist spots. W.Trevor's short prose is marked by valid details, diversity of points of view and narrative voices. He united the features of "short story" and "tale". His short story "Broken Homes" may be the illustration of these characteristics. Ukrainian short fiction is represented nowadays by the works of Valeriy Shevchuk, Dmitro Keshelia, Galina Pagutiak, Lubov Ponomarenko, Vasil' Gabor, Oleg Govda, Vasil' Trubay, Volodimir Danilenko, Yevgeniya Kononenko, Yuriy Vinnichuk etc. We direct our attention to V.Trubay. Trevor and Trubay are different in many aspects: age, language, partly outlook, even aesthetics. But there are moments of correspondence between them: two letters in their surnames; realistic codes mixed with imagination in their short stories; dramatic impulse (as in Trubay's story "Tang"); presence of the superhuman, Supreme Being (as in Trubay's "Apocalypse"); absurd, Kafka's images. Trevor's and Trubay's short stories are structured according to morphologic norm of this genre. One more aspect establishes relation between the stories of two masters – their concern to visual, plastic aspects of the world, their attention to details.
Genre characteristics of the trevor's short story: ukrainian reflections
Keywords: short story; tale; tradition; experiment; visualization; новела; оповідання; традиція; експеримент; візуалізація